Estimating Spillovers from Publicly Funded R&D: Evidence from the US Department of Energy - Myers, Kyle R.; Lanahan, Lauren (American Economic Review, 2022)
We quantify the magnitude of R&D spillovers created by grants to small firms from the US Department of Energy. Our empirical strategy leverages variation due to state-specific matching policies, and we develop a new approach to measuring both geographic and technological spillovers that does not rely on an observable paper trail. Our estimates suggest that for every patent produced by grant recipients, three more are produced by others who benefit from spillovers. Sixty percent of these spillovers occur within the United States, and many of them occur in technological areas substantially different from those targeted by the grants. (JEL H81, L25, O33, O34, Q40)